DOMINASI PENILAIAN HASIL DALAM PRAKTIK ASESMEN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH: SYSTEMATIC LITERATURE REVIEW - Nabila Sethia Izzati; Abdul Munip; Shohib (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the dominance of outcome-based assessment in Islamic Religious Education (PAI) learning in schools through a Systematic Literature Review (SLR). The article selection process was assisted by Rayyan and reported by adapting the PRISMA flow, including identification, screening, eligibility assessment, and inclusion of final articles. Articles were collected from Scopus and Google Scholar using search strings related to PAI assessment, learning evaluation, outcome-based assessment, formative and summative evaluation, affective assessment, psychomotor assessment, and authentic assessment. The initial search identified 500 articles published between 2016 and 2025. After title and abstract screening, 95 articles were selected for full-text review, and 12 relevant articles were finally analyzed. The findings show three main patterns. First, PAI assessment is still dominated by cognitive tests, scores, written assignments, and summative evaluation. Second, affective and psychomotor assessments are less systematically implemented due to limited instruments and teachers’ assessment literacy. Third, authentic, formative, reflective, and performance-based assessments are needed to balance outcome-based assessment with process-oriented assessment. This study contributes to the development of PAI assessment by offering a thematic synthesis that emphasizes the need for more holistic, contextual, and balanced assessment practices, particularly in line with the implementation of the Merdeka Curriculum.